1993
DOI: 10.1093/cvr/27.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Correlated expression of atrial myosin heavy chain and regulatory light chain isoforms with pressure overload hypertrophy in the non-human primate

Abstract: There is tight coupling between the expression of myosin subunit isoforms under pathological conditions from a primate species closely related to humans. The data suggest that the synthesis of these subunits of myosin may be coordinated at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…13,17 On the basis of the present studies, the postnatal MLC isoform switch in the left ventricle of the neonate may facilitate ejection against the increased systemic arterial pressure that occurs at parturition. In addition, several studies have demonstrated expression of the ventricular isoform of MLC2 in the atria of hypertrophied hearts of both humans and experimental animals in response to pathological conditions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…13,17 On the basis of the present studies, the postnatal MLC isoform switch in the left ventricle of the neonate may facilitate ejection against the increased systemic arterial pressure that occurs at parturition. In addition, several studies have demonstrated expression of the ventricular isoform of MLC2 in the atria of hypertrophied hearts of both humans and experimental animals in response to pathological conditions.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, several studies have demonstrated expression of the ventricular isoform of MLC2 in the atria of hypertrophied hearts of both humans and experimental animals in response to pathological conditions. [13][14][15][16][17] Wanker et al 15 found MLC2v in atrial samples from patients with a variety of cardiomyopathies, and the level of ventricular isoform expression correlated with the severity of heart failure. Likewise, Cummins 16 reported that the degree of pressure-overload hypertrophy in humans is the most significant factor influencing ventricular MLC2v isoform expression in the human atria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this notion, TG1 ventricles had significant down-regulation of myosin light chain 2 ventricular isoform (MLC2V) (63 Ϯ 19 versus 100 Ϯ 17, P ϭ 0.0116), a down-regulation also observed in tissues from hypertrophic human hearts and in hypertrophic and hypertensive primate and rodent models. [25][26][27][28] SERCA2a, a marker of heart failure 29 -31 was not significantly different in the ventricles or atria of either line. It is apparent from the literature that different patterns of dysregulation for hypertrophic markers characterize specific murine models; importantly, although some markers may not be up-regulated in specific models, an increase in ␣-skeletal actin is always observed.…”
Section: Bi-atrial Enlargement Cardiac Hypertrophy and Dilationmentioning
confidence: 79%
“…Although the complete functional pattern of this protein remains unclear, it is supposed that MYL7 is a player in cardiac development and contractility. In baboons, levels of ALC-2 expression were shown to be correlated to the expression levels of MHC-alpha in the atrial myocardium (Henkel et al, 1993). Strikingly, the abundance alteration of MYL7 switched during the development of the DMD pigs.…”
Section: The Altered Abundance Of Several Proteins Directly Related Tmentioning
confidence: 93%